Giant urethral stone with diverticulum; a case report - Asad Ramzan; Adeen Akram; Suaiba Saif; Farhan Jamshed; Nauman Khalid (Journal of University Medical & Dental College, 2021)
Urethral calculi are rare and represent 1-2% of all urinary stone diseases. Rarely, calculus grows to large size and are labeled as a "giant urethral calculus". A 75-year-old male came to the OPD of Madinah Teaching Hospital Faisalabad with a chief complaint of suprapubic pain, penile pain, and hard mass on the left side of the scrotum and anterior perineum. The patient had a significant history of undergoing debridement for Meleney’s and Fournier’s gangrene, along with suprapubic cystostomy done about 1.5 years back. Physical examination revealed a solid mass with dimensions 6x7 cm on the left side of the scrotum and anterior perineum (left periurethral area). Open surgery was performed. A huge stone, 6x6cm, was removed. Diverticulae were excised, and urethroplasty was performed. A catheter was removed on the 21st postoperative with a satisfactory urinary stream.